TEAMSGAMES TOURNAMENT (TGT): MEMADUKAN UNSUR COMPETITIVE DAN COOPERATIVE DALAM RANGKA PENINGKATAN KUALITAS PEMBELAJARAN PKN - Nadziroh Nadziroh (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2015)
Â Abstract: Many researches has been done in searching the advantages and disadvantages, both Cooperative and competitive model of teaching. Each of them has many advantages as well as disadvantages. Accordingly, the task of teachers is to take the advantages and eliminate its disadvantages.This article tries to propose Team Game Tournament as a meansin integrating cooperative and competitive aspects of instructional activity.with is distinctive feature, TGT can combines both cooperative and competitive spirits of student. As a result, hopefully, student achievement will increase.Theachers of PKn should change their circumstances, chiefly their traditional instructional practices. Implementation of TGT in some right occasion is one of means in increasing instructional effectiveness.